Water consumption in the Middle East and North Africa (MENA) region: a virtual water approach - Timmerman, Matthew (AUC Knowledge Fountain, 2013)
As the population of the MENA region rises, virtual water import is increasing, evident by striking food import figures in many of the region's countries. This is not a new development, it has long been the case that MENA countries have used the import of high water content agricultural commodities as a mechanism for covering domestic food consumption via external water. This said, as climate induced global water scarcity and population driven global water demand increase simultaneously, the MENA region's practice of importing water via agricultural commodities should gain increasing attention. The research herein quantitatively assesses MENA nations' virtual water import determinants. Virtual water import stands as a function of changing regional variables including: population and economic growth, as well as strain on domestic water resources. While virtual water import from food commodities has sustained the MENA for decades, it cannot be assumed that the region will always remain a beneficiary of global water trade. Consequently, the region represents the geographic starting point for the global discussion on the sustainability of virtual water trade practices in the changing world.